TEACHING COMPUTATIONAL ELECTROMAGNETICS AT NORTHEASTERN UNIVERSITY: FROM PCS TO SUPERCOMPUTERS - Rappaport, Carey M. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
As supercomputers become more accessible and as inexpensive personal computers become more powerful, the numerical modeling of electromagnetic fields in non-idealized geometries becomes increasingly practical. To enable graduate students to solve useful real-world problems, Northeastern University’s course ECE 3347: Computational Methods of Electromagnetics teaches the important techniques of field and wave simulation, making use of a variety of programming languages, graphics packages, and computer systems which range from home computers to the most powerful supercomputers. Strong emphasis on algorithm design and computer testing helped motivate students to develop an understanding of the major issues involved in using computers to simulate electromagnetics problems. [Vol. 8, No. 1, (1993), Special Issue on Computer Applications in Electromagnetics Education, pp 157-165]